Self-Assembly as a Technique for Peptide-Based Materials - Juan Wang; Xuehai Yan (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2015)
Molecular self-assembly is a key function in biology and has been developed as an elegant technique for fabrication of various complex structures and functional materials. Key importance for structural formation in terms of self-assembly is molecular recognition pertaining to intermolecular weak interactions such as hydrophobic interactions, hydrogen bonds, π-π stacking, electrostatic forces and dipole-dipole interactions etc. A combination of several kinds of such weak interactions can govern molecular organization and thus ordered supramolecular architectures. Among molecular building blocks are the bioinspired and bioderived molecules including peptides and proteins. Peptides consisting of several amino acids are most popular over decades for development of molecular biomaterials owing to ease of availability, programmable molecular motif, biocompatibility and biodegradation, flexible functionality and low cost-effectiveness. The nanostructures and materials assembled using peptides as building blocks have presented an important potential for green-life new technology and biomedical applications. In this opinion, self-assembly and application of several kinds of peptides including aromatic dipeptides, polypeptides, amphiphilic peptides, lipopeptides, and inorganic-hybridized peptide will be stated briefly.